Participatory Valuation of Ecosystem Services: A Case Study - Kiktenko, Ludmilla; Zhumagazina, Balzhan; Zhakenova, Saltanat; Nangia, Vinay; Dessalegn, Bezaiet (Springer, 2018)
Valuation of ecosystem services is important for generating evidence for improved management of natural resources. Contingent Valuation (CV) is a common approach used to establish stakeholders’ stated preference by assessing their willingness to pay (WTP) or willingness to accept (WTA) monetary compensation for forgone services. This paper proposes another alternative - Willingness to Forego (WTF) – a variant of the concept of opportunity costs for soliciting stakeholders’ valuation of eco-system services, and to validate recommendations from two watershed models. The concept is tested in three villages located at the beginning, middle and tail end of the Turkistan canal in South Kazakhstan. Stakeholders’ WTF current benefits by changing their current management and use of irrigation water in lieu of optimal conservation measures proposed by the models were first established. Then stakeholders’ responses were analyzed from the perspective of agricultural risk-management, to understand drivers of their preferences. Despite their stated preference to conserve ecosystem services, agents were found to opt for options that offer maximum current benefits and minimum risks. Lack of information on potential effects of proposed conservation measures pushes farmers into the realm of uncertainty which influences their WTF. While the results remain specific to this case, they are consistent with literature that link farmers’ behaviors to ecological performances. The findings also present important basis for expanding the discussion on ecosystem valuation methods, and offers insight to decision makers to be cognizant of the need to maintain the delicate balance between ensuring current livelihoods and sustainable management of ecosystem services